Phase separation in solvent extraction of copper or nickel from acidic solution using a sulfonic acid (HDNNS) and a carboxylate ester (4PC). Issue 6 (3rd June 2019) - Luo, Yuqing; Hu, Huiping; Wang, Yongxi; Hu, Fang; Zhu, Shan; Zhang, Shuaifei; Zhang, Ying; Li, Shengkang; Wang, Junya
Abstract: Phase separation behavior is a critical character in determining the usefulness of a solvent extraction system in hydrometallurgy. A survey of the synergistic mixture containing dinonylnaphthalene sulfonic acid (HDNNS) and 2-ethylhexly 4-pyridinecarboxylate ester (4PC) for the extraction of copper or nickel from acidic single metal sulfate solution has been carried out to suggest how the physicochemical properties (density, viscosity and interfacial tension) and the morphology of the reverse micelles in the loaded organic phase affect the phase separation behavior in this paper. The specific settling rates (SSR), physicochemical properties, metal concentration and the excess water uptake (the content of water solubilized into the water pool of the reverse micelles) in the loaded organic phase during the extraction of Cu(II)/Ni(II) have been measured. The results show that the most effective parameters affecting the phase separation behavior are the viscosity and the excess water uptake of the loaded organic phase. We assume that the deceleration of the SSR is mainly due to the apparent increase of these two parameters or in a microscopic view, the apparent change of the morphology of the reverse micelles in the loaded organic phase. The small angle X-ray scattering (SAXS) results provide a direct evidence of such microstructural changes and well supports our assumption. Graphical Abstract: